Selection of Black Bengal buck based on fertility and field progeny performance - Afrin, S; Debnath, S; Rahman, ANMI; Paul, RC; Khandoker, MAMY (Bangladesh Journal of Animal Science, 2014)
This study was aimed for selection of Black Bengal bucks based on their fertility and the performance of their progeny in field condition. Data on buck were collected from a nucleus breeding flock and on progeny at field level. The traits considered were birth weight, weight at every 3-m interval up to 12 m of age. Average daily gain (g/day) on 90 progeny produced from 10 bucks and semen parameters on these bucks were collected. Heritability estimates obtained for birth weight, 3, 6, 9 and 12-m weights and average daily gain of progeny were found to be 0.41±0.08, 0.49±0.07, 0.46±0.08, 0.48±0.28, 0.50±0.09 and 0.49±0.06, respectively. The high heritability estimates of body weights indicated that there is a good opportunity for genetic improvement of this trait in a selection scheme. Heritability estimates obtained for semen volume, sperm concentration, sperm motility, sperm livability and normal sperm were 0.11±0.04, 0.25±0.07, 0.13±0.08, 0.12±0.08 and 0.06±0.03, respectively. The highest non return rate was observed in bucks of 32, 52 and 57 (66.67±6.75%). The lowest was found in buck 48 (41.67±5.65%). Among 10 bucks, first 3 top buck IDs were 52, 57 and 54 on the basis of BV at birth weight. Selection index of bucks for all traits was calculated and bucks were ranked accordingly. The highest selection index of three bucks ID were 52, 7 and 4 (1009.39, 934.595 and 865.808, respectively). It can be concluded that these top ranking three bucks can be selected and conserved for production and preservation of frozen semen for long term use. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19379 Bang. J. Anim. Sci. 2014. 43 (1): 11-20